DYNAMICS OF MENTAL EDUCATION OF PRESCHOOL CHILDREN - Lytvyn, Vadim (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article presents the results of the control stage of the dissertation research and highlights the data obtained regarding the dynamics of mathematical development of older preschool children. The purpose of the article is to present the results of the control stage of the dissertation research and highlight the data obtained regarding the dynamics of mathematical development of older preschool children. The realization of the goal involves solving the following tasks: 1) to analyze the dynamics of mathematical development of older preschool children during the control stage of the pedagogical experiment; 2) to study and summarize the data obtained. The following methods were used to solve the above-mentioned problem: analysis of philosophical, psychological-pedagogical and methodical literature on the research problem; methods of pedagogical diagnostics (a diagnostic technique for studying the level of mathematical development of older preschool children). Based on the study of the initial level of mathematical development of older preschool children, game technology for the mathematical development of older preschool children was developed and implemented. The technology implementation process was based on a specially created integrated model, which provided for managerial, methodical and technological levels of its implementation. The purpose, tasks, content, forms and methods of organizing mental education for mathematical development of older preschool children were defined and implemented in the process of experimental and pedagogical activity, the result of which was the achievement of a high level of development by older preschool children. The content of the formation of the levels of mathematical development was focused on the formation of cognitive, emotional, value and activity components, which acquired appropriate specifications. The success of the formation of high and sufficient levels of mathematical development was determined by the use of active forms and methods, the implementation of the optimal principles laid down as the basis of the game technology of mathematical development. The stable dynamics of increasing the levels of formation of the mathematical development of older preschool children testifies to the pedagogical expediency and effectiveness of the developed and theoretically grounded game technology of mental education, as well as the pedagogical conditions for its effective implementation.